Gas transport through cork: Modelling gas permeation based on the morphology of a natural polymer material - Brazinha, Carla; Fonseca, Ana P.; Pereira, Helena; Teodoro, Orlando M. N. D.; Crespo, João G. (Journal of Membrane Science, 2013)
Natural polymers have been studied during the last years for the transport and separation of liquid and gas mixtures, in terms of solubility and permeability data, and their structure and mechanical properties have been characterised. However, no transport models have been reported, relating transport with the material morphology. Cork is a natural cellular material containing three structural polymers (suberin, lignin and polysaccharides). Cork is considered a natural polymer, with economic relevance due to its sealing, non-toxic, stable and low-density properties. Cork was characterised in this work in terms of its solubility and permeability data in relation to various gases with different molecular mass: He, O2, N2, CO2 and 1,1,1,2-tetraﬂuoroethane (R134a). A morphological analysis of the structure of the cork sample chosen in this work was also performed using SEM (scanning electron microscopy) and TEM (transmission electron microscope) image analysis, which took into account the variation of each relevant structural parameter. A transport model was developed supported on the morphology of cork characterised in this work. The transport model developed considers that gas permeation occurs through the plasmodesmata, which are channels with approximately 100 nm of diameter that cross the cell walls of the cork cells. It was found that gas transport follows a Knudsen mechanism, as proved by the gas permeability behaviour with increasing gas molecular mass, with a negligible contribution of viscous transport to the total ﬂux.
Keywords: Cork; Gas permeation; Knudsen transport; Natural polymers; solubility; Solution–diffusion model

Permeability of Cork for Water and Ethanol - Fonseca, Ana Luisa; Brazinha, Carla; Pereira, Helena; Crespo, João G.; Teodoro, Orlando M. N. D. (Journal of Agricultural and Food Chemistry, 2013)
Transport properties of natural (noncompressed) cork were evaluated for water and ethanol in both vapor and liquid phases. The permeability for these permeants has been measured, as well as the sorption and diffusion coefficients. This paper focuses on the differences between the transport of gases? relevant vapors and their liquids (water and ethanol) through cork. A transport mechanism of vapors and liquids is proposed. Experimental evidence shows that both vapors and liquids permeate not only through the small channels across the cells (plasmodesmata), as in the permeation of gases, but also through the walls of cork cells by sorption and diffusion as in dense membranes. The present study also shows that cork permeability for gases was irreversibly and drastically decreased after cork samples were exposed to ethanol or water in liquid phase.
doi: 10.1021/jf4015729doi: 10.1021/jf4015729The following values have no corresponding Zotero field: publisher: American Chemical Society
Keywords: Cork; diffusion; permeability; sealing properties; Sorption; water transport